PERSEPSI WAJIB PAJAK PADA PP 46 TAHUN 2013 DI KOTA BOJONEGORO - Nurul Mazidah; Arif Farida (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2014)
Since the First Tax reform (tax reform first) in 1984, tax is expected to Main Source of APBN Budget Financing maintained its continuity. This research is aimed(1) To know how perception or level of understanding taxpayer about PP 46 the beginning started in July 2013. (2)To know the Taxpayer Compliance hearts Paying Taxes According to PP 46, whether taxpayer direct accept determination PP number 46 2013. The informants hearts husband used study is 4 (four) taxpayer Personal have the turnover under 4,8 billion and 2 (two) representing corporate taxpayer. The data are collected using a Trianggulasi (Combined)method, which is inductive data analysis, qualitative research articles commercial more emphasize the significance of generalization. Results of our research is based on the findings of research already knows most of the big informants on the Tax Regulation, but their hearts will yet fill truly understand husband regulation (pp 46). Conclusion of our research is mostly big informant has Perception that incriminating initials PP 46.